Análise do tempo de absorção de preservante pela madeira de eucalyptus spp. Com diferentes diâmetros. - (:unkn) unknown (Universidade Federal do Pampa, 2011)
The wood is a product that has always been in the service of man. Since the early times in the course of time the techniques of woodworking has been developingsteadily and wood is gaining more importance to humanity with their products and derivatives. The wood of Eucalyptus spp. is widely used on farms in the form of awooden fence posts for being easy to purchase and its duration being pretty good in extreme conditions. This study aimed to determine the absorption time of apreservative solution for the wood of Eucalyptus spp. with different diameters. Thestudy was performed using fences of Eucalyptus spp. with dimensions ranging from 9 to 15 cm in diameter and 2.18 to 2.26 m in length. The timber was placed in abarrel of 200 liters to absorb the chemical solution, the chemical used was BAC.The amount of solution that was absorbed by the timber was checked daily. All the three repetitions were performed with fences of different diameters. In the study it was found that the repetition that contained the least amount of wood was that it took more time to absorb the solution and that the repetition was performed on sunny days and higher temperature showed a faster absorption.
Keywords: Madeira; Preservação; Seiva; Moirões; Wood; Preservation; Sap; CNPQ::CIENCIAS AGRARIAS